2022
DOI: 10.3390/ani12070808
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Based on Regularly Recorded Claw Health Data of Austrian Dairy Cattle for Implementation in the Cattle Data Network (RDV)

Abstract: While benchmarking is already used for the assessment of performance gaps in cattle herd management and welfare concerns, its application to quantifying claw health performance is relatively new. The goal here was to establish a benchmarking system for claw health in Austrian dairy cattle. We used electronically registered claw health data of cows from 512 dairy herds documented by professional hoof trimmers, culling data from the same herds, and locomotion scores taken at regular milk performance testings in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
1
16
2
Order By: Relevance
“…It is characterized by ulcerative or proliferative skin lesions that are typically located at the plantar aspect of the interdigital cleft and can result in severe lameness (Evans et al, 2016;Orsel et al, 2018;Plummer and Krull, 2017). The contagious nature and unsatisfactory treatment responses of BDD (Ariza et al, 2017;Capion et al, 2018;Orsel et al, 2018) result in prevalences of up to 91% at the herd level and 41% at the cow level (Rodriguez-Lainz et al, 1998;Cruz et al, 2001;Relun et al, 2013;Jury et al, 2021;Kofler et al, 2022). In the United States, up to 75% of dairy farms and approximately 19% of the dairy cows are affected with BDD (UW-Extension Dairy Team, 2016;USDA, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by ulcerative or proliferative skin lesions that are typically located at the plantar aspect of the interdigital cleft and can result in severe lameness (Evans et al, 2016;Orsel et al, 2018;Plummer and Krull, 2017). The contagious nature and unsatisfactory treatment responses of BDD (Ariza et al, 2017;Capion et al, 2018;Orsel et al, 2018) result in prevalences of up to 91% at the herd level and 41% at the cow level (Rodriguez-Lainz et al, 1998;Cruz et al, 2001;Relun et al, 2013;Jury et al, 2021;Kofler et al, 2022). In the United States, up to 75% of dairy farms and approximately 19% of the dairy cows are affected with BDD (UW-Extension Dairy Team, 2016;USDA, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, lameness incidence risks were high on most participating farms, highlighting an ongoing issue in some dairy herds. However, this is not representative for all Austrian dairy farms, as data from a recent benchmarking study for claw health suggested that many dairy farms in Austria have a good claw health status and lameness incidence rates of less than 24.6% for the herds in the 25th percentile [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…All LKV employees were part of previous studies and were well trained in assessing the LCS and BCS [ 22 , 23 , 51 ]. To ensure the interobserver reliability for this study, all of them participated in a training on a commercial dairy farm in October 2019 and within two weeks thereafter completed an online video test where different video scenarios of nonlame (LCS 1) and lame cows (LCS 2–5) were presented.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations